Modeling and simulation of acid generation in anion-bound chemically amplified resists used for extreme ultraviolet lithography. (12th February 2015) - Komuro, Yoshitaka; Kawana, Daisuke; Hirayama, Taku; Ohomori, Katsumi; Kozawa, Takahiro
Abstract: Extreme ultraviolet (EUV) lithography is the most promising candidate technique for the high-volume production of semiconductor devices with half-pitches of sub-10 nm. An anion-bound polymer, in which the anion part of onium salts is polymerized, has attracted much attention from the viewpoint of the control of acid diffusion. In this study, we modeled the acid generation processes in the anion-bound chemically amplified resists upon exposure to EUV radiation and developed a Monte Carlo simulation code. Using the developed simulation code, the dependence of the quantum efficiency of acid generation on the concentration of acid generator units was calculated. The calculated quantum efficiencies well agreed with the experimental values with a fitting error of less than 10%. The thermalization distance was considered to be approximately 3 nm. The blur of proton distribution intrinsic to the reaction mechanisms of anion-bound chemically amplified resists was roughly estimated to be 4.5–6.5 nm.